2014
DOI: 10.1165/rcmb.2013-0056oc
|View full text |Cite
|
Sign up to set email alerts
|

A Novel In Vitro Model to Study Alveologenesis

Abstract: Many pediatric pulmonary diseases are associated with significant morbidity and mortality due to impairment of alveolar development. The lack of an appropriate in vitro model system limits the identification of therapies aimed at improving alveolarization. Herein, we characterize an ex vivo lung culture model that facilitates investigation of signaling pathways that influence alveolar septation. Postnatal Day 4 (P4) mouse pup lungs were inflated with 0.4% agarose, sliced, and cultured within a collagen matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
(38 reference statements)
2
29
0
Order By: Relevance
“…Application of a supraphysiological dose of TGFβ, or TGFβ induced via hyperoxia, arrests alveolar formation (Vicencio et al, 2004). In contrast, one study has shown that antibodyblockade of TGFβ disrupts alveologenesis in lung explants (Pieretti et al, 2014). We found TGFβ signaling in SCMFs to be important in regulating elastic fiber formation.…”
Section: Pdgfra Controls a Second Tier Of Signaling Networkmentioning
confidence: 64%
“…Application of a supraphysiological dose of TGFβ, or TGFβ induced via hyperoxia, arrests alveolar formation (Vicencio et al, 2004). In contrast, one study has shown that antibodyblockade of TGFβ disrupts alveologenesis in lung explants (Pieretti et al, 2014). We found TGFβ signaling in SCMFs to be important in regulating elastic fiber formation.…”
Section: Pdgfra Controls a Second Tier Of Signaling Networkmentioning
confidence: 64%
“…Similarly, the use of decellularized lungs permits the unique opportunity to define the ECM-derived signals that direct lung cell fate during development, and how these signals are disrupted during injury 197 . Along these lines, the initial flurry of interest in the application of precision-cut lung sections to study lung alveolarization 198 has not yet found widespread application. Both organoids and lung sections present a wonderful opportunity for advanced molecular analyses to understand cell-cell and cell-matrix interactions and developmental pathways pertinent to BPD pathobiology.…”
Section: Understanding Bpd Pathobiology – Future Directionsmentioning
confidence: 99%
“…For the quantitative morphometry, multiple plastic-embedded 1-mm sections of the entire mouse lung were stained with toluidine blue according to established protocols (20). For assessment of elastin morphology, 5-mm lung sections were stained with Hart's resorcin-fuchsin solution, without and with prior oxidation with potassium permanganate and clearing with oxalic acid, and counterstained with tartrazine as described previously (21). Bright-field microscopy was used to generate the lung images; the elastin images were constructed from a z-stack of lung images using extended depth-of-field focusing (22).…”
Section: Lung Histological Stainingmentioning
confidence: 99%